2020
DOI: 10.3390/nano10102007
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Induced Synthesis of Non-Target Biosafety Silver Nanoparticles for the Control of Rice Bacterial Diseases

Abstract: Silver is an important and efficient bactericide. Nanoscale silver has a large specific surface area, high target adhesion, strong permeability and high bactericidal activity. At present, the control of plant bacterial diseases is difficult, and the resistance of plant bacterial pathogens develops rapidly. Silver nanoparticles are expected to become a new generation of agrochemical to control plant bacterial diseases. In this study, a simple and green natural sunlight-induced method was used to prepare carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Antibacterial mechanisms of nanosilver particles have been reported in several studies; however, they remain controversial. The following three antibacterial mechanisms of nanosilver particles are widely accepted: (1) nanosilver particles directly damage the outer membrane, cell wall, and cell membrane of bacteria, changing the permeability of the cell membrane and finally causing cell leakage. , (2) The presence of Ag ions and Ag particles in bacterial cells leads to the production of reactive oxygen species (ROS), which cause oxidative stress and ultimately apoptosis . (3) Silver ions can bind to thiol groups on bacterial proteins, resulting in DNA degradation and metabolic dysfunctions, such as respiratory reactions, lipid synthesis, and protein synthesis impairment .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Antibacterial mechanisms of nanosilver particles have been reported in several studies; however, they remain controversial. The following three antibacterial mechanisms of nanosilver particles are widely accepted: (1) nanosilver particles directly damage the outer membrane, cell wall, and cell membrane of bacteria, changing the permeability of the cell membrane and finally causing cell leakage. , (2) The presence of Ag ions and Ag particles in bacterial cells leads to the production of reactive oxygen species (ROS), which cause oxidative stress and ultimately apoptosis . (3) Silver ions can bind to thiol groups on bacterial proteins, resulting in DNA degradation and metabolic dysfunctions, such as respiratory reactions, lipid synthesis, and protein synthesis impairment .…”
Section: Results and Discussionmentioning
confidence: 99%
“…While selenite (product of selenium dioxide and water) has been identified as a highly toxic chemical, 38 the morphology of nanoparticles may show reduced toxicity. 39 In this study, in vitro cell viability tests were performed to preliminarily explore the cytotoxicity of selenium (IV) oxide and selenium (0) nanoparticles. The preosteoblast cell line (MC3T3) was used to evaluate the cell survival rate at the test concentration.…”
Section: Evaluation Of Cytotoxicitymentioning
confidence: 99%
“…Studies have shown that AgNPs have strong microorganism-inhibiting properties [ 10 ] and possess free radical scavenging and anti-inflammatory properties [ 11 ]. Additionally, AgNPs have been found to have wound healing properties, anti-tumor [ 12 ], antiviral, antibacterial, and anti-angiogenic effects [ 13 ]. AgNPs have been shown to trigger apoptosis and reduce the level of matrix metalloproteinase in wounds, limiting angiogenesis [ 14 ] and vascular permeability with the help of growth factors, i.e., VEGF, interleukin (IL)-1, and advanced glycation in endothelial cells of the retina [ 15 ].…”
Section: Introductionmentioning
confidence: 99%